Plant defense : warding off attack by pathogens, herbivores and parasitic plants - Walters, Dale R. (Wiley-Blackwell, 2011)
Plant Defense provides comprehensive coverage of the range of different organisms that plants need to fend off, describes how plants coordinate their ddefenses against multiple attacks, explains the evolution of defense in plants, and how plant defences are exploited in crop protection strategies